Validation of a Novel Immunoline Assay for Patient Stratification according to Virulence of the Infecting Helicobacter pylori Strain and Eradication Status. (30th May 2017) - Formichella, Luca; Romberg, Laura; Meyer, Hannelore; Bolz, Christian; Vieth, Michael; Geppert, Michael; Göttner, Gereon; Nölting, Christina; Schepp, Wolfgang; Schneider, Arne; Ulm, Kurt; Wolf, Petra; et al.
Abstract : Helicobacter pylori infection shows a worldwide prevalence of around 50%. However, only a minority of infected individuals develop clinical symptoms or diseases. The presence of H. pylori virulence factors, such as CagA and VacA, has been associated with disease development, but assessment of virulence factor presence requires gastric biopsies. Here, we evaluate the H. pylori recom Line test for risk stratification of infected patients by comparing the test score and immune recognition of type I or type II strains defined by the virulence factors CagA, VacA, GroEL, UreA, HcpC, and gGT with patient's disease status according to histology. Moreover, the immune responses of eradicated individuals from two different populations were analysed. Their immune response frequencies and intensities against all antigens except CagA declined below the detection limit. CagA was particularly long lasting in both independent populations. An isolated CagA band often represents past eradication with a likelihood of 88.7%. In addition, a high recom Line score was significantly associated with high-grade gastritis, atrophy, intestinal metaplasia, and gastric cancer. Thus, the recom Line is a sensitive and specific noninvasive test for detecting serum responses against H. pylori in actively infected and eradicated individuals. Moreover, it allows stratifying patients according to their disease state.